Digital technology impact on film distribution - Dabrovolskas, Audrius (Information & Media, 2016)
The article analyses changes of the film distribution model. Due to the influence of digital technologies, new forms of film distribution, such as the internet, enabled uploading and downloading, video on demand service. The article also explores how these film distribution forms affect the information behaviour of a film consumer. It is important to emphasize that there are positive and negative factors, which have a significant influence on the film distribution market and on the film industry in general. The Lithuanian film industry faces positive trends because the number of domestic films has increased and more Lithuanian films are being screened in the film theaters. However, one of the most important negative aspects is piracy which highly affects distributors, and especially independent distributors. The main form of film distribution in Lithuania is still theater distribution which generates the best economic outcome. The usage of the DVD format is decreasing, and the video on demand service has the growing potential in the Lithuanian film industry.